The protease SPRTN and SUMOylation coordinate DNA-protein crosslink repair to prevent genome instability - Ruggiano, Annamaria; Vaz, Bruno; Kilgas, Susan; Popović, Marta; Rodriguez-Berriguete, Gonzalo; Singh, Abhay N.; Higgins, Geoff S.; Kiltie, Anne E.; Ramadan, Kristijan (Cell reports (Cambridge), 2021)
DNA-protein crosslinks (DPCs) are a specific type of DNA lesion in which proteins are covalently attached to DNA. Unrepaired DPCs lead to genomic instability, cancer, neurodegeneration, and accelerated aging. DPC proteolysis was recently identified as a specialized pathway for DPC repair. The DNA-dependent protease SPRTN and the 26S proteasome emerged as two independent proteolytic systems. DPCs are also repaired by homologous recombination (HR), a canonical DNA repair pathway. While studying the cellular response to DPC formation, we identify ubiquitylation and SUMOylation as two major signaling events in DNA replication-coupled DPC repair. DPC ubiquitylation recruits SPRTN to repair sites, promoting DPC removal. DPC SUMOylation prevents DNA double-strand break formation, HR activation, and potentially deleterious genomic rearrangements. In this way, SUMOylation channels DPC repair toward SPRTN proteolysis, which is a safer pathway choice for DPC repair and prevention of genomic instability. [Display omitted] •SUMOylation and ubiquitylation enable DPC repair during DNA replication•Resolution of ubiquitylated and SUMOylated DPCs requires the protease SPRTN•Inactivation of SUMOylation after DPC formation activates homologous recombination•DPC SUMOylation and SPRTN prevent recombination-dependent genomic instability Ruggiano et al. show that ubiquitylation and SUMOylation of DNA-protein crosslinks is linked to repair by SPRTN during DNA replication. Blocking SUMOylation causes double-strand breaks and switches the repair pathway to homologous recombination, potentially causing chromosomal rearrangements and genomic instability. Inactivation of DPC repair causes synthetic lethality in recombination-defective cells.